CONTROLLED CHAOS : Essays on Malaysia's New Politics Beyond Mahathirism and The Multimedia Super Corridor - Azly Rahman,deauthor 256946 (Petaling Jaya, Selangor : Strategic Information and Research Development Centre (SIRD), 2015)
Includes bibliographical references